Outcomes of Autologous Stem Cell Transplantation as a Consolidative Strategy for the Treatment of Primary and Isolated Secondary Central Nervous System Diffuse Large B Cell Lymphomas - Sahin, Ugur; Gokmen, Ayla; Soydan, Ender; Urlu, Selin M.; Merter, Mustafa; Gokgoz, Zafer; Ozcan, Muhit (Cig Media Group, Lp, 2023)
Higher rates of non-relapse mortality observed in primary central nervous lymphoma patients > 60 years of age after high dose chemotherapy and autologous stem cell transplantation (HDC/ASCT) lead to significantly lower survival rates when compared to younger patients. Not only age, but also comorbidities, clinical performance and response to induction therapy correlates with outcomes.Introduction: Standard consolidation for primary diffuse large B cell lymphoma (DLBCL) of the central nervous system (CNS) (PCNSL) is not established. This single center, retrospective observational study aims to define the outcomes of consolidative high dose chemotherapy and autologous stem cell transplantation (HDC/ASCT) in patients with PCNSL and isolated secondary CNS DLBCL (SCNSL) and evaluate the prognostic factors. Patients and Methods: All consec-utive patients performed an HDC/ASCT for PCNSL or isolated SCNSLs between October 2012 and February 2022 were identified. Primary endpoints were progression-free survival (PFS) and overall survival (OS). Results: Among 35 patients included, 28 had PCNSL and 7 had isolated SCNSL. Median age was 51 (16-78). Males constituted 48.6%. Median follow-up after HDC/ASCT was 42.0 months. MATRIX (51.4%) and TEAM (80.0%) were the most frequent regimens of induction and conditioning, respectively. OS and PFS 1-and 2-year after HDC/ASCT were 68.0%, 57.0%, 58.0%, 48.0%, respectively. Increasing age, poor performance and comorbidities were associated with lower OS and PFS and higher non-relapse mortality (NRM). Complete response (CR) 1 at HDC/ACST was independently associated with higher OS and PFS [hazard ratio (HR): 4.67 and 6.99, respectively]. Conclusion: In patients < 60 years consolida-tive HDC/ASCT yields promising OS and PFS. Patients > 60 years may less likely benefit from consolidative HDC/ASCT and should be studied further in trials of novel agents, lower doses of consolidative radiotherapy and dose-adjusted conditioning regimens. Not only age, but also comorbidities, clinical performance and response to induction correlate with outcomes. Patients with isolated SCNSL may achieve similar outcomes.
Keywords: Central nervous system lymphoma; Consolidation